Manajemen Program Penguatan Pendidikan Karakter Religius di MA Swasta Al-Ulum Medan - Rhaudatul Jannah; Ellisa Fitri Tanjung (LP. Ma'arif Janggan Magetan, 2024)
Religious character education in schools is part of a program formed by the school to provide guidance for students in behaving and acting in accordance with religious teachings. The purpose of this study is to describe how the implementation of the religious character education strengthening program is carried out at the Al - Ulum Private Madrasah in Medan to instill religious character in students. The method used in this study is a qualitative method with data collection techniques derived from observation, field notes and documentation. The results of the study show that in forming and instilling the religious character of students at the Al- Ulum Private Madrasah, Medan, it is carried out through a religious character education strengthening program involving schools and educators. The form of the religious character education strengthening program implemented at the Al - Ulum Private Madrasah is the implementation of tahsin al-Quran before the start of learning activities until the completion of the al-Quran and the habit of praying dhuha on Thursdays and Saturdays, and the implementation of these two programs is structured and routine. The implementation of this religious character education strengthening program has a positive impact on students, namely students become accustomed to reading the Koran and are accustomed to performing the Dhuha prayer every day.